2019
DOI: 10.17554/j.issn.2224-3992.2019.08.823
|View full text |Cite
|
Sign up to set email alerts
|

Low Adherence To Nutritional Recommendations In Patients With Cirrhosis: A Prospective Observational Study

Abstract: AIM:The aim of the study was to evaluate patients' adherence to the current nutritional recommendations adapted to the individual clinical status. MATERIALS AND METHODS: 192 outpatients with cirrhosis were prospectively evaluated. 161 were considered at risk of impaired nutrition as they present at least one of the following factors: altered body mass index score, non-volitional body weight changes, ascites, peripheral edema, hepatic encephalopathy, or diabetes.Patients at risk were offered a nutritional asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Dietary habits of patients may have changed due to the disease or deteriorated nutritional status. However, studies have shown that habitual diet in general is largely stable for at least 5 years 53 , 54 and many patients with CP or LC fail to adhere to disease-specific dietary recommendations 55 , 56 . Moreover, in CP and LC other mechanisms such as an increased resting energy expenditure due to systemic inflammation or malabsorption can contribute to impaired nutritional status.…”
Section: Limitationsmentioning
confidence: 99%
“…Dietary habits of patients may have changed due to the disease or deteriorated nutritional status. However, studies have shown that habitual diet in general is largely stable for at least 5 years 53 , 54 and many patients with CP or LC fail to adhere to disease-specific dietary recommendations 55 , 56 . Moreover, in CP and LC other mechanisms such as an increased resting energy expenditure due to systemic inflammation or malabsorption can contribute to impaired nutritional status.…”
Section: Limitationsmentioning
confidence: 99%
“…A total of 16 quantitative studies (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) were retrieved (cohort, n = 12; case-control, n = 3; randomized controlled trial, n = 1) with the most common topic being knowledge assessment of patients (41)(42)(43)48,52,55), care partners (48), or physicians (45,49). Several studies, mostly from North America and Europe, also evaluated HE medication adherence of the patients (40,44,47,51,54)…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Adherence to cirrhosis specific nutrition guidelines is consistently low across studies. In 78 patients (HE, 23%) where 80% were at risk of malnutrition, only 12% and 9% met their daily protein and calorie intakes, respectively (50). In an Indian study of 251 patients (mean MELD-Na 17.2), 16% ate a late evening snack and only 21% ate more than three meals or snacks per day (53).…”
Section: Quantitative Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…We have recently performed an observational prospective study specifically designed to assess the food intake in a cohort of outpatients with cirrhosis at different stages of severity [34]. The Emilia-Romagna ethic committee (CE-AVEC) reviewed and approved the study (number of approval 33/2014/U/Sper) and all patients gave informed consent before the inclusion.…”
Section: Studies Focused On Food Intake In Patients Awaiting Ltmentioning
confidence: 99%